Pengaruh Struktur Modal dan Kinerja Keuangan Terhadap Harga Saham Pada PT. Adaro Energy, Tbk. - Muhibah Muhibah (AkMen JURNAL ILMIAH, 2020)
The purpose of this study was to determine the effect of capital structure and financial performance to stock price at PT. Adaro Energy, Tbk. The types of data that the writer used are qualitative data and quantitative data. The source of data was used is secondary data. The analytical method used is multiple regresion analysis. The result showed that partially the capital structure proxied by DER had positive effect but not significant effect on stock price, while the financial performance proxied by ROA had postive and significant effect on stock price. Simultaneosly capital structure and financial performance have a positive and insignificant effect on stock price. R2value is 0,959 which means that 59,5% stock price can be explained by capital structure and financial performance.